2011
DOI: 10.1038/cdd.2011.98
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 serves ER stress-triggered apoptosis via selective activation of the IRE1–JNK pathway

Abstract: Mammalian target of rapamycin (mTOR) has a key role in the regulation of an array of cellular function. We found that rapamycin, an inhibitor of mTOR complex 1 (mTORC1), attenuated endoplasmic reticulum (ER) stress-induced apoptosis. Among three major branches of the unfolded protein response, rapamycin selectively suppressed the IRE1-JNK signaling without affecting PERK and ATF6 pathways. ER stress rapidly induced activation of mTORC1, which was responsible for induction of the IRE1-JNK pathway and apoptosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
221
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(239 citation statements)
references
References 39 publications
14
221
4
Order By: Relevance
“…TSC deficiency is functionally linked to mTORC2 inactivation as well as mTORC1 hyperactivation, both of which are thought to be major players of TSC disease (8,13). Previous studies proposed that induction of UPR is an important pathologic feature of TSC disease that contributes to critical functional abnormalities in insulin/IGF1 action and cell survival (26,40,49). These studies also suggested that mTORC1 hyperactivation by TSC deficiency increases the sensitivity of cells to ER stress-mediated death revealing an unusual property of mTOR to promote cell death under certain circumstances (26,40,49).…”
Section: Discussionmentioning
confidence: 99%
“…TSC deficiency is functionally linked to mTORC2 inactivation as well as mTORC1 hyperactivation, both of which are thought to be major players of TSC disease (8,13). Previous studies proposed that induction of UPR is an important pathologic feature of TSC disease that contributes to critical functional abnormalities in insulin/IGF1 action and cell survival (26,40,49). These studies also suggested that mTORC1 hyperactivation by TSC deficiency increases the sensitivity of cells to ER stress-mediated death revealing an unusual property of mTOR to promote cell death under certain circumstances (26,40,49).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been further elucidated, in tubular cells, that activation of pro-apoptotic pathways can be mediated by the induction of ER stress. Not only was mTORC1 determined to function downstream of ER stress in these cells, but subsequent mTORC1 activity involved pathways culminating in IRE1-JNK activation (Kato et al 2012). Interestingly, inhibition of mTORC1 with rapamycin under the same physiological conditions selectively inhibited the IRE1 pathway.…”
Section: Adaptive Responses To a Perturbed Er In Diabetic Ptcsmentioning
confidence: 97%
“…The speculation that mTORC1 may be involved in the pathogenesis of DN came from the observation that an inhibitor of mTORC1 (rapamycin) attenuates renal hypertrophy in experimental models of DN (Sakaguchi et al 2006). Rapamycin selectively restores integrity of the podocyte foot processes through the stabilisation of the protein nephrin in the filtration barrier and reduces subsequent tubular and glomerular damage (Inoki et al 2011, Kato et al 2012. Nephrin is an integral podocyte protein involved in the retention of larger macromolecules in the blood as well as playing a role in the membrane docking of the insulin-sensitive glucose transporter, GLUT4 (Coward et al 2007).…”
Section: Mechanisms Culminating In a Stressed Diabetic Podocyte Ermentioning
confidence: 99%
“…Three to seven days after the UUO (day 3 and 7), left kidneys were removed and processed for histopathological analysis, immunohistochemistry and northern/western blot analyses. 34 In some experiments, partial UUO (mild ligature) was induced using a nylon thread (0.6 mm in diameter). 35 Individual groups contained 3-4 mice.…”
Section: Formazan Assaymentioning
confidence: 99%
“…We therefore used a mild-ligature model of UUO 34 to examine the effect of this agent at a later time period. In this experimental model, induction of collagen and a-SMA was mild, and treatment with 3 0 -deoxyadenosine modestly attenuated UUO-induced expression of type I collagen and a-SMA even at day 7 (Supplementary Figure S8).…”
Section: Lack Of Eif2a-mediated Translational Suppression For the Effmentioning
confidence: 99%